A department of methodology can coordinate transdisciplinary sport science support - Rothwell, M.; Davids, K.; Stone, J. A.; O'Sullivan, M.; Vaughan, J.; Newcombe, D. J.; Shuttleworth, R. (Journal of Expertise, 2020)
In the current sporting landscape, it is not uncommon for professional sport teams and organizations to employ multidisciplinary sport science support teams. In these teams and organizations, a "head of performance" may manage a number of sub-discipline specialists with the aim of enhancing athlete performance.Despite the best intentions of multidisciplinary sport science support teams, difficulties associated with integrating sub-disciplines to enhance performance preparation have become apparent. It has been suggested that the problem of integration is embedded in the traditional reductionist method of applied sport science, leading to the eagerness of individual specialists to quantify progress in isolated components. This can lead to "silo" working and decontextualized learning environments that can hinder athlete preparation. To address this challenge, we suggest that ecological dynamics is one theoretical framework that can inform commonprinciples and language to guide the integration of sport science sub-disciplines in a Department of Methodology. The aim of a Department of Methodology would be for group members to work within a unified conceptual framework to (1) coordinate activity through shared principles and language, (2) communicate coherent ideas, and (3) collaboratively design practice landscapes rich in information (i.e., visual, acoustic, proprioceptive and haptic) and guide emergence of multi-dimensional behaviors in athlete performance.